Suicide prevention during disasters and public health emergencies: a systematic review - Reifels, Lennart; Krysinska, Karolina; Andriessen, Karl (Frontiers in Public Health, 2024)
Background Disasters and public health emergencies increasingly affect populations around the world, posing significant wide-ranging challenges for societies as well as for effective public health and suicide prevention. Intervention research is essential to inform evidence-based responses. Yet, despite evident public concern and growing research interest in heightened suicide risks and impacts, little is known about effective suicide prevention interventions in these contexts. We conducted a systematic review to examine the outcomes of suicide prevention strategies implemented in disasters and public health emergencies. Methods We searched five databases (Medline, Embase, PsycINFO, Web of Science, PTSDpubs) from inception to December 2022 for peer-reviewed quantitative studies that reported relevant intervention outcomes (changes in the frequency of suicide, suicide attempts, self-harm) for populations affected by disasters and public health emergencies. We assessed the quality of eligible studies using the Quality Assessment Tool for Quantitative Studies, and distilled review findings through narrative synthesis. The study protocol was registered with PROSPERO (CRD42021276195). Results Ten eligible and mostly observational studies were included in this review, which examined a range of universal, selective, and indicated interventions. Three of five studies of interventions in public health emergencies indicated the potential effectiveness and buffering effects of generic disaster related mental health support, access to urban parks, as well as the beneficial role of video-enabled tablets in facilitating treatment access and outcomes. Similarly, three of five studies of interventions in disaster contexts provided evidence of the beneficial role of universal economic security measures, national gun laws and buy back schemes, and volunteer-delivered mental health support. Overall, four of six studies with favorable outcomes examined interventions specifically deployed in disaster or public health emergency contexts, whereas two studies examined ongoing existing interventions. Three studies, respectively, of suicide prevention focused interventions or generic interventions reported favorable outcomes. The quality of included studies was variable, with two studies being rated as ‘strong’, four studies rated as ‘moderate’, and four studies rated as ‘weak’. Conclusion Notwithstanding the limited scope and variable quality of published evidence, our review findings highlight the breadth of interventions that have been applied in such contexts with some success. There is a need for further research on effective interventions and intervention adaptations to inform evidence-based suicide prevention responses to disasters and public health emergencies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021276195, PROSPERO ID CRD42021276195.